2020
DOI: 10.1016/j.ekir.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Randomized Controlled Trial of a Standard Versus a Modified Low-Phosphorus Diet in Hemodialysis Patients

Abstract: Introduction:The standard low-phosphorus diet restricts pulses, nuts, and whole grains and other high phosphorus foods to control hyperphosphatemia. We conducted a randomized controlled trial to evaluate the effectiveness, safety, and tolerability of the modified diet, which introduced some pulses and nuts, increased the use of whole grains, increased focus on the avoidance of phosphate additives, and introduced the prescription of low-biological-value protein such as bread.Methods: We conducted a multicenter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This feeding study supported the postprandial safety and tolerability of the modified versus the standard diet, and allowed for further evaluation of the modified diet a randomised controlled trial of 74 patients over one month which concluded that the diet was well tolerated and was associated with similar phosphate and potassium control but with a wider food choice and greater fiber intake than the standard diet 64 . This feeding study should be repeated, with larger numbers in the afternoon or evening.…”
Section: Discussionmentioning
confidence: 65%
“…This feeding study supported the postprandial safety and tolerability of the modified versus the standard diet, and allowed for further evaluation of the modified diet a randomised controlled trial of 74 patients over one month which concluded that the diet was well tolerated and was associated with similar phosphate and potassium control but with a wider food choice and greater fiber intake than the standard diet 64 . This feeding study should be repeated, with larger numbers in the afternoon or evening.…”
Section: Discussionmentioning
confidence: 65%
“…A study by Shah et al reported decreases in urinary phosphorus and calcium excretion as well as blood calcium levels in type 2 diabetes patients who consumed a high‐fibre diet (50 g/day) for 6 weeks 21 . Byrne et al also reported that a 1‐month study of two diets to control hyperphosphataemia in adults on haemodialysis showed no significant difference in serum phosphate levels, despite significantly higher dietary fibre intake in subjects in one of the groups (both groups had equivalent dietary phosphorus intake) 22 . Because most of these studies were relatively long term, it is difficult to make a clear comparison with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the bioavailability of inorganic K + (as provided in the SSaSS trial) is not necessarily equivalent to that of K + derived from a fruit- or vegetable-rich diet, as we already know from the strikingly different intestinal bioavailability of phosphate from inorganic (i.e., additives) versus plant-derived phosphate sources [ 19 , 58 ]. The anion linked to K + , other nutrients (e.g., magnesium, vitamin K), protein (with lower phosphate bioavailability), higher fiber content (enhancing intestinal motility and short-chain fatty acid production), or alkali (neutralising acidosis and its harmful consequences) in plant-based or adapted “healthy” diets may have contributed to the outcomes of different studies [ 25 , 59 , 60 , 61 ]. These factors may also explain the unclear correlation between dietary and serum K + [ 51 , 61 ].…”
Section: Dietary K + and Ckd: A Word Of Cautionmentioning
confidence: 99%
“…These factors may also explain the unclear correlation between dietary and serum K + [ 51 , 61 ]. As was recently reported [ 25 , 61 ], the traditional dietary paradigm limiting the intake of fruits and vegetables to CKD patients because of their high K + content is rapidly evolving due to the potential pleiotropic benefits deriving from a fundamentally vegetarian or Mediterranean-adapted diet [ 59 , 60 ]. These also include improvement in gut dysbiosis and decreased production of harmful uraemic toxins, together with reductions in inflammation and oxidative stress [ 25 ].…”
Section: Dietary K + and Ckd: A Word Of Cautionmentioning
confidence: 99%